Debt Maturity, Underinvestment Problem And Corporate Value - Lee, Karren -Hwei Khaw; Lee, Benjie Chien Jiang (Asian Academy of Management (AAM), 2016)
This study examines how Malaysian public listed firms with low and high corporate values use debt maturity as a tool to mitigate underinvestment problem. This study employs panel data methodology instead of the commonly used pooling regression. Results show that firms with low Tobin's Q ratio, a proxy for corporate value, maintain lower level of long-term debt to mitigate agency costs of debt caused by underinvestment problem, whereas firms with high Tobin's Q ratio are indifferent with the debt maturity decision. This study extends the literature on the determinants of debt maturity structure by highlighting the importance of recognising the firms by the corporate values in relation to the underinvestment problem. The findings also provide additional justification for the existing literature in explaining the negative relationship between agency costs of debt and debt maturity structure using a sample of firms from a developing market